2019
DOI: 10.1063/1.5108865
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an impulse pressure generator based on the drop-weight method

Abstract: An optimized impulse dynamic pressure generator based on a drop-weight method was developed as a secondary standard. The impulse pressure generator was characterized in detail using various parameters in order to obtain a proper reference dynamic pressure, to calibrate a dynamic pressure sensor. Both a hardware filter and a software filter were successfully employed to eliminate unavoidable noise when the impulse pressure was generated. Five variables were considered to optimize the system. A larger effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Invariant weight methods such as the minimum variance method and the minimum absolute value method, variable weight method, etc. are based on the idea of minimising the prediction error of the combined model [10][11][12][13]. However, some studies have found that if the selected single model is not appropriate, it may also lead to worse prediction performance of the final combined model [14], and thus precise analysis of data with different characteristics is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Invariant weight methods such as the minimum variance method and the minimum absolute value method, variable weight method, etc. are based on the idea of minimising the prediction error of the combined model [10][11][12][13]. However, some studies have found that if the selected single model is not appropriate, it may also lead to worse prediction performance of the final combined model [14], and thus precise analysis of data with different characteristics is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To simplify the structure, Chen used a profiled cam to drive a single-rod hydraulic cylinder to generate the pressure impulse wave; the rotational speed of the cam indicates the frequency of the output signal [15]. Drop-weight method too has been commonly applied to develop impulse pressure generators [16,17]; however, this method can hardly provide even a rough water hammer wave. Theimer and Kolle designed a hydraulic pulse valve with a rotary spool and improved the sleeve to achieve longer wear life and better performance; these features will can help establish an open-loop system that generates the required pressure impulse signals [18].…”
Section: Percentage Of One Circlementioning
confidence: 99%